2021
DOI: 10.14740/cr1243
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Modulators: The New Era of Medical Therapy for Systolic Heart Failure and Hypertrophic Cardiomyopathy

Abstract: A new uprising pharmacological treatment for systolic heart failure and hypertrophic cardiomyopathy demonstrates very promising results the last years. Myosin modulators have already been tested in numerous studies. Myosin inhibitor (mavacamten) and myosin stimulator, (omecamtiv mecarbil) exhibit their effect by improving clinical outcomes, as well as reducing morbidity and mortality. More studies are however required for further evaluation and particularly effect on sarcomeric level. Side effects of both phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The Morrow operation is the gold standard for the treatment of HCM. Although Lekaditi Dimitra and others believe that medical treatment can improve the outcome, its effect is not as clear as that of the operation [ 6 , 7 ]. Havndrup et al believe that compared with other treatments, the Morrow operation is still the best in terms of postoperative effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Morrow operation is the gold standard for the treatment of HCM. Although Lekaditi Dimitra and others believe that medical treatment can improve the outcome, its effect is not as clear as that of the operation [ 6 , 7 ]. Havndrup et al believe that compared with other treatments, the Morrow operation is still the best in terms of postoperative effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PIONEER-HCM trial has demonstrated that mavacamten led to decrease of pressure gradient, as well as increased peak oxygen consumption (VO 2 ). Finally, attention should be paid to the combination with beta-blocker, verapamil or disopyramide, primarily since with myosin inhibitors, it may come to drop in LVEF and hypotension [ 33 ]. Ongoing trials may highlight this important aspect.…”
Section: The Futurementioning
confidence: 99%
“…Since these proteins act in a reversible and fast way, small molecules can act as useful modulators of their functionality, leading to the development of novel therapeutic agents. [34][35][36] X-ray structures of 2JJ9 37 and 2XEL 38 (Fig. 2a and b) were obtained in the absence (2JJ9) and presence (2XEL) of an allosteric myosin inhibitor, named pentachloropseudilin (PClP).…”
Section: Analysis Of Biological Oá á áV Contactsmentioning
confidence: 99%
“…Since these proteins act in a reversible and fast way, small molecules can act as useful modulators of their functionality, leading to the development of novel therapeutic agents. 34–36…”
Section: Introductionmentioning
confidence: 99%